2022
DOI: 10.1029/2022ja030861
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Origin of Tidal Oscillations in the Ionospheric Transition Region With EISCAT Radar and Global Simulation Data

Abstract: The ionospheric dynamo region marks the transition from a collision-dominated plasma below approximately 90 km to a nearly collisionless plasma above approximately 150 km. Across this transition region, ion/electron gyrofrequencies Ω i/e are of the same order as collision frequencies ν in/en . Therefore, Pedersen and Hall conductivities maximize at these altitudes. Pedersen and Hall currents perpendicular to the magnetic field close the global magnetospheric field-aligned current system. Dynamic processes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…One major assumption for the present study was the application of TIE‐GCM neutral winds and ion‐neutral collision frequencies for both measurement and model calculations. It is possible to calculate neutral winds from EISCAT CP2 measurements (Brekke et al., 1973; Günzkofer et al., 2022; Nozawa et al., 2010) but this, in turn, requires knowledge of the ion‐neutral collision frequency. The ion‐neutral collision frequency can be measured from dual‐frequency EISCAT experiments (Grassmann, 1993; Günzkofer, Liu, et al., 2023; Günzkofer, Stober, et al., 2023; Nicolls et al., 2014) which is not possible in combination with beam‐swing measurements.…”
Section: Discussionmentioning
confidence: 99%
“…One major assumption for the present study was the application of TIE‐GCM neutral winds and ion‐neutral collision frequencies for both measurement and model calculations. It is possible to calculate neutral winds from EISCAT CP2 measurements (Brekke et al., 1973; Günzkofer et al., 2022; Nozawa et al., 2010) but this, in turn, requires knowledge of the ion‐neutral collision frequency. The ion‐neutral collision frequency can be measured from dual‐frequency EISCAT experiments (Grassmann, 1993; Günzkofer, Liu, et al., 2023; Günzkofer, Stober, et al., 2023; Nicolls et al., 2014) which is not possible in combination with beam‐swing measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In the following, we apply this method to an AGW-TID event that occurred during the MLT fall transition. The fall transition is connected to the autumn equinox and has been shown to have a major impact on atmospheric tides in the MLT region (Stober et al, 2021d;Pedatella et al, 2021;Günzkofer et al, 2022). Other studies suggest that there is also an impact on the gravity wave forcing from below (Placke et al, 2015) which, in consequence, will alter the observed wave parameters in the ionosphere.…”
Section: Agw-tid Parameters During the Fall Transitionmentioning
confidence: 99%
“…Strong changes in AGW-TID activity in the MLT are caused by the seasonal variation of mesospheric mean winds (Stober et al, 2021d), especially during the spring and fall equinox transitions. The latter in particular has been shown to impact tidal waves in the mesosphere (Stober et al, 2020;Pedatella et al, 2021) and possibly well up in the thermosphere (Günzkofer et al, 2022). Investigating the impact of the MLT fall transition, the change of the MLT wind system around the autumn equinox (Stober et al, 2021d), on AGW-TIDs is one of the central topics of this manuscript.…”
Section: Introductionmentioning
confidence: 98%
“…Whereas ground-based remote sensing facilities have been providing continuous measurements of key LTI parameters as a function of altitude and local time, and are currently a main source of information on ion-neutral interactions across the LTI (see, e.g., Wahlund et al (1992); Rishbeth and Van Eyken (1993); and, as examples of recent studies, e.g. the work by Tesema et al (2022); Günzkofer et al (2022)), there are limitations of remote sensing methods in addressing the science questions outlined herein. These limitations are related to the temporal and spatial resolution that ground-based instruments can provide as well as to the need for co-temporal, co-spatial measurements of all parameters involved.…”
Section: On the Need For In Situ Lower Thermosphere-ionosphere Measur...mentioning
confidence: 99%